DESAIN BUKU TEKS AJAR BAHTSUL KUTUB - Muhammad Natsir (Universitas Islam Nahdlatul Ulama Jepara, 2016)
ABSTRACTThe course of Bahtsul Kutub 1, as one of the supporting courses of the study program PAI, provides the provision of the ability to understand Islamic education and understand the character of diversity of Sunni Islam through the understanding of Arabic texts with the provision of vocabulary mastery and sentence structur patterns. The results of research in this article describes the quality of teaching materials in the form of textbooks for the subject of Bahtsul Kutub 1 which is used as a lecture material in the study program PAI FTIK Unisnu Jepara. The technique of developing this textbook is through four stages, namely planning, organizing, executing and evaluating. Content of the book is complemented with vocabulary meanings and examples of translation model of sentence pattern. The result of the reviewer??s score indicated that the book is categorized Good with an average score of 43.8 with high criterion level on the truth and conceptual variables. This is shown in the test results of practicality by students with an average score of 106.1 which shows the criteria Very Good which means practical for being used in learning process. Keywords: development, textbook, Bahtsul Kutub